Development and validation of a two-dimensional liquid chromatography method for therapeutic drug monitoring of pyrotinib in human plasma - Gao, Chunxia; Cao, Yuzhi; An, Mengna; Li, Zhihui; Meng, Chao; Lan, Jingjing; You, Haisheng; Chen, Siying (Frontiers in Pharmacology, 2025)
ObjectiveTo develop and validate a method for therapeutic drug monitoring (TDM) of pyrotinib in human plasma using two-dimensional liquid chromatography (2D-LC) system.MethodThe plasma samples were pretreated with acetonitrile for protein precipitation. The mobile phase consisted of two parts: a first-dimensional mobile phase (methanol, acetonitrile, and 65 mmol/L ammonium phosphate in a ratio of 1:3:3, V/V/V) and a second-dimensional mobile phase (acetonitrile, isopropanol, and 10 mmol/L ammonium phosphate in a ratio of 16:7:1, V/V/V). The analysis cycle time was completed within 9.50 min. The method was validated for linearity, recovery, precision, accuracy, and stability.ResultsPyrotinib demonstrated excellent linearity within the range of 10.10–810.40 ng/mL with regression equation y = 556.4044× + 462.40 (R2 = 0.9995). The relative recovery rate of plasma samples was stable and reproducible, ranging from 96.82% to 100.12%. The intra-day and inter-day precisions were ≤5.30% and ≤3.80% for pyrotinib concentrations, respectively. Stability tests confirmed that pyrotinib in plasma remained stable under the following conditions: room temperature for 8 h, 4 °C for 48 h, −20 °C for 3 weeks, three freeze-thaw cycles. This method was validated in twenty patients with advanced HER2-positive breast cancer (dose range: 240–400 mg/day) The trough and peak plasma concentrations of pyrotinib ranged from 17.75–92.56 ng/mL and 51.17–232.94 ng/mL, respectively, which demonstrated significant pharmacokinetic heterogeneity.ConclusionThe developed 2D-LC analytical method not only demonstrates good precision, accuracy, recovery, and stability, but also is simple, rapid, feasible, and practical for TDM. It can be used for the concentration monitoring of pyrotinib in clinic, providing more scientific evidence for clinical practice.